Periplasmic chaperone FkpA reduces extracytoplasmic stress response and improves cell-surface display on Escherichia coli - Narayanan, N.; Chou, C. P. (Enzyme and Microbial Technology, 2008)
When enhanced yellow fluorescence protein (EYFP) was displayed on the cell surface of Escherichia coli using EstA* as a carrier, the integrity of the cell envelope was compromised and cell physiology was severely impaired, resulting in poor display performance. Coexpression of fkpA, a gene encoding periplasmic chaperone, was demonstrated to be effective for restoring cell physiology and enhancing display performance. On the basis of monitoring the promoter activities of degP, rpoH, and cpxP under various culture conditions, we also showed that cell-surface display using EstA* as a carrier induced the extracytoplasmic stress response and the stress could be partially alleviated by fkpA coexpression. (C) 2008 Elsevier Inc. All rights reserved.